The problem of peer review in screen production: exploring issues and proposing solutions. Issue 1 (2nd January 2016) - Glisovic, Smiljana; Berkeley, Leo; Batty, Craig
ABSTRACT: With traditional academic work, the process of peer review is seemingly clear – work is refereed as a way of gatekeeping ideas and research contributions, to ensure it is not publicly available until it has passed a test of rigour, originality, clarity and significance to the field. Those with assumed knowledge of the discipline are the said gatekeepers, tasked with assessing the work on the basis of disciplinary knowledge and general research expertise. This often rests on the notion that the research and knowledge are made explicit in the writing. This is problematic for non-traditional academic work, such as screen production and media art, because a key value in this kind of work is the ability to communicate implicitly and differently from what can be articulated within the parameters of written, academic language. This tension between implicit and explicit knowledge claims has been one source of difficulty for evaluating and therefore rewarding creative practice research. In this paper, we draw on a recent gathering of screen production academics, the two-day Sightlines: Filmmaking in the academy festival and conference, to help us discuss the complexities of peer reviewing screen production works for the academy, and to help us point towards possible solutions. We focus specifically on where and in what form the articulation of research might happen to assist the peer reviewing process, where the common approach is to write a research statement that makes explicit the methodologies undertaken and the new knowledge being claimed. This has incited some protest from within the screen production community: for example, how do we account with language for the very thing that is in excess of language, the contribution that finds its unique place outside of language and within the moving image? We therefore also discuss the dialogic relationship between art and writing, and the kinds of relationality that might be created to help make room for the 'in-articulable'. In short, how research and new knowledge in a screen work might be illuminated, and how an academic peer might therefore evaluate it. We conclude by discussing an approach we are currently taking to develop an online, refereed publication for screen production works, the Sightlines Journal, in response to both the current literature on the topic and the gathering of discipline academics. Given the various contexts in which these questions arise in relation to screen production research (during the writing of a PhD, in the examination process, and in professional environments), we address them accordingly as individual yet interwoven discussions driven by the shared need to find workable solutions to recurring problems.